Single‐Ion Implantation: Position‐Controlled Functionalization of Vacancies in Silicon by Single‐Ion Implanted Germanium Atoms (Adv. Funct. Mater. 21/2021). (24th May 2021) - Achilli, Simona; Le, Nguyen H.; Fratesi, Guido; Manini, Nicola; Onida, Giovanni; Turchetti, Marco; Ferrari, Giorgio; Shinada, Takahiro; Tanii, Takashi; Prati, Enrico
Abstract : In article number, 2011175, Simona Achilli, Enrico Prati, and co‐workers report on the controlled creation of individual vacancies in silicon by implanting Ge atoms via single ion implantation, the quantum transport model of a disordered 1D array of Ge‐V complexes, and its experimental characterization. Peculiar activation energies are found from cryogenic to room temperature. Image created using ArtBreeder AI agent.